Comparing the given equation with the standard equation "Pdx+Qdy+Rdz=0," we get
"P=z^2,Q=z^2-2yz,R=2y^2-yz-xz"
The given equation is homogeneous of degree 2. Now first of all, we test the condition of integrability.
"P\\left(\\frac{\\partial R}{\\partial y}-\\frac{\\partial Q}{\\partial z}\\right)-Q\\left(\\frac{\\partial R}{\\partial x}-\\frac{\\partial P}{\\partial z}\\right)+R\\left(\\frac{\\partial Q}{\\partial x}-\\frac{\\partial P}{\\partial y}\\right)\\\\\n=z^2(4y-z-2z+2y)-(z^2-2yz)(-z-2z)+(2y^2-yz-xz)(0-0)\\\\\n=6yz^2-3z^3+3z^3-6yz^2=0"
Hence, the equation is integrable.
Substitute "x=uz,y=vz" into the equation.
This implies that, "dx=udz+zdu,dy=vdz+zdv"
"z^2(udz+zdu)+z^2(1-2v)(vdz+zdv)+z^2(2v^2-v-u)dz=0"
With this, the coefficient of "dz" will be 0. SO, we have;
"z^3du+z^3(1-2v)dv=0"
Divide through by "z^3"
"du+(1-2v)dv=0"
Integrate through
"u+v-v^2=C"
But, "u=\\frac{x}{z},y=\\frac{y}{z}"
"\\frac{x}{z}+\\frac{y}{x}-\\frac{y^2}{z^2}=C\\\\\nxz+yz-y^2=Cz^2"
Hence, the general solution of the equation is "xz+yz-y^2=Cz^2" .
Comments
Leave a comment